Peningkatan Perilaku Sadar Periodontal Sehat Pada Ibu Hamil Melalui Edukasi dan Pemeriksaan Indeks CPITN Di Desa Paddinging - Muhammad Jayadi Abdi; Sari Aldilawati; Muhammad Fajrin Wijaya (PT.Mantaya Idea Batara, 2022)
Background: Health is the most important part of human life, physically and spiritually healthy, including pregnant women. To achieve optimal dental and oral health in toddlers and pregnant women, it is carried out regular treatment. Treatment can be started to pay attention to the consumption of Moranan, cleaning plaque and the remaining ganan brushing teeth regularly and correctly, cleaning tartar, patching delangs and tooth extraction. The health of the oral cavity of pregnant women affects the condition of the badi they contain. Method: This type of research is a quantitative research in pre -design research experimental design. In this design uses the design of a pretest posttest group without comparable or control. Results: The average value of the mother's knowledge before being given treatment is 70,167 standard debiation as large as 14,999, whereas after being given.67 the average value of the mother's test.67. This shows an increase in the average value of mothers' knowledge after being born. Increasing healthy periodontal conscious behavior in pregnant women through counseling. DISCUSSION: Prayer One strategy for changes in knowledge is the information of information to increase knowledge that raises awareness in the end. Conclusion: There is a change in the knowledge of women and pregnant women about the importance of maintaining dental and oral health especially periodontal.